2019
DOI: 10.1080/2000625x.2019.1579631
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D and diabetic foot complications

Abstract: Background : Foot complications such as ulceration and neuropathy are common complications of diabetes mellitus (DM). Previous reports have demonstrated a possible increased risk of these complications in diabetic patients with low levels of serum vitamin D. Objectctive : The purpose of this study is to compare serum vitamin D levels in diabetic patients with and without Charcot neuroarthropathy (CN), peripheral arterial disease (PAD), infection (DFI), ulceration (DFU), and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 40 publications
2
41
0
3
Order By: Relevance
“…ABI, a useful marker for detection of peripheral artery disease (PAD) or atherosclerosis at other vascular sites [34], has been demonstrated to be independently associated with DPN [35]. In the present study, we have revealed that the T2DM subjects in the higher serum albumin quartiles exhibited higher levels of DBP, eGFR, ABI, and lower Cr, CysC, and ACR compared with subjects in the lowest quartile, and serum albumin levels were positively associated with DBP, and negatively with Cr, CysC, and ACR after the adjustments, indicating that serum albumin may be associated with DN and PAD as diabetic micro-and macrovascular complications, respectively, which are consistent with those of many previous reports [15,[36][37][38]. Zhang et al conducted a study of 188 patients with T2DM and biopsy-proven DN followed up for at least one year, and found that serum albumin level was signi cantly associated with proteinuria, renal function, and glomerular lesions, and hypoalbuminemia was associated with a poorer renal prognosis [36].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…ABI, a useful marker for detection of peripheral artery disease (PAD) or atherosclerosis at other vascular sites [34], has been demonstrated to be independently associated with DPN [35]. In the present study, we have revealed that the T2DM subjects in the higher serum albumin quartiles exhibited higher levels of DBP, eGFR, ABI, and lower Cr, CysC, and ACR compared with subjects in the lowest quartile, and serum albumin levels were positively associated with DBP, and negatively with Cr, CysC, and ACR after the adjustments, indicating that serum albumin may be associated with DN and PAD as diabetic micro-and macrovascular complications, respectively, which are consistent with those of many previous reports [15,[36][37][38]. Zhang et al conducted a study of 188 patients with T2DM and biopsy-proven DN followed up for at least one year, and found that serum albumin level was signi cantly associated with proteinuria, renal function, and glomerular lesions, and hypoalbuminemia was associated with a poorer renal prognosis [36].…”
Section: Discussionsupporting
confidence: 91%
“…Changes of plasma concentration and structural modi cation of albumin induced by high glucose or free radicals impair its antioxidant properties and aggravate oxidative stress [19]. Several previous studies have explored the association of serum albumin with the development of DPN, and provided inconsistent results [12][13][14][15]. Iwasaki et al reported that serum albumin was independently related to the median motor nerve conduction velocity and minimum F-wave latency in 130 Japanese patients with T2DM, and was signi cantly inversely associated with the presence of DPN [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single high dose of oral vitamin D could substantially improve the brachial artery flow-mediated vasodilatation by 2.3%. Moreover, vitamin D has been suggested as an immune stimulant 25 . Urashima et al 26 suggested that vitamin D supplementation can reduce the risk of influenza A in schoolchildren.…”
Section: Discussionmentioning
confidence: 99%